The Impact of Social Entrepreneurship on Reducing Economic Inequality, Community Self-reliance, and Business Innovation in Urban Areas: A Case Study in Jakarta, Indonesia - Iwan Harsono; Ihsan Ro'is; Wahyunadi Wahyunadi; Emi Salmah (West Science Journal Economic and Entrepreneurship, 2023)
With an emphasis on Jakarta, Indonesia, this study examines the relationship between company innovation, community self-reliance, and economic gap reduction and social entrepreneurship success in metropolitan settings. Using a quantitative methodology, 170 participants in the sample shared details about their entrepreneurial endeavors. The measurement model was validated by confirmatory factor analysis, which also confirmed the validity and reliability of the chosen constructs. Significant positive correlations between closing the economic gap, fostering community self-reliance, corporate innovation, and the effectiveness of social entrepreneurship were found using structural equation modeling. The findings were shown to be robust, and the distinctiveness of the constructs was confirmed using discriminant validity analysis and bootstrapping approaches. The model's strong explanatory ability was demonstrated by the R-Square values. The practical implications of the study's findings for policymakers, entrepreneurs, and communities in Jakarta pertain to creating an environment that is favorable for social entrepreneurship.